2017
DOI: 10.1177/0363546517740575
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Matrix-Induced Chondrogenesis: A Systematic Review of the Clinical Evidence

Abstract: This systematic review reveals a paucity of high-quality, randomized controlled studies testing the AMIC technique versus established procedures such as microfracture or ACI. Evidence is insufficient to recommend joint-specific indications for AMIC. Additional nonbiased, high-powered, randomized controlled clinical trials will provide better clinical and structural long-term evidence, thus helping to define possible indications for this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 63 publications
(125 reference statements)
1
59
0
5
Order By: Relevance
“…A possible translational clinical scenario where such scaffolds could be implanted into the subchondral bone would be as an adjunct to marrow stimulation techniques for cartilage repair (6). When implanted into the subchondral penetrations, such porous TGF-b1-releasing scaffolds could induce chondrogenesis of migrating MSCs into the cartilage defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible translational clinical scenario where such scaffolds could be implanted into the subchondral bone would be as an adjunct to marrow stimulation techniques for cartilage repair (6). When implanted into the subchondral penetrations, such porous TGF-b1-releasing scaffolds could induce chondrogenesis of migrating MSCs into the cartilage defect.…”
Section: Discussionmentioning
confidence: 99%
“…Cell condensation occurs in the cartilage defect, precursor mesenchymal cells then divide and differentiate into chondrogenic and osteogenic lineages, maturate, and deposit extracellular matrix. This process is tightly controlled by growth and transcription factors, paracrine interactions with articular cartilage that surrounds the defect, and other environmental factors (1,6). As a result, a new cartilaginous repair tissue that is rich in type II collagen and proteoglycans fills the defect, whereas endochondral ossification restores the subchondral bone.…”
mentioning
confidence: 99%
“…Since more recent ACI versions are based on collagen carriers (27), the chondrocytes were cultured on collagen type II-coated membranes in a 24-wells transwell system as described previously (28). Passage two chondrocytes were seeded on inserts (PICM01250, Millipore) with a hydrophilic poly-tetrafluoroethylene (PTFE) membrane at 1.6×10 6 cells/cm 2 in DMEM with 2% w/v ITSx (51500, Invitrogen), 2% w/v ascorbic acid (A8960, Sigma-Aldrich), 2% w/v human serum albumin (HS-440, Seracare Life Sciences), 100 units/mL penicillin, 100 μg/mL streptomycin, and 10 ng/mL TGF-β 2 (302-B2, R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…18,44 Autologous Matrix-induced Chondrogenesis AMIC was first introduced in 2010 and describes a combination of bone marrow stimulation, for example, MFx with the placement of a acellular collagen matrix onto the cartilage defect. [61][62][63] The first steps of AMIC resemble those of the MFx Fig. 3 Sagittal proton-density-weighted fat-suppressed MR images (a) 6 months, (b) 1 year, and (c) 2 years following autologous osteochondral transplantation (OAT) in a 45-year-old male patient (same patient as in Fig.…”
Section: Osteochondral Allograft Transplantationmentioning
confidence: 99%
“…Additionally, the type I/III collagen matrix is trimmed to the size of the cartilage defect and fixated using either sutures or fibrin glue. 62 AMIC is generally used to treat articular cartilage defects > 2 cm. 2,63 In many clinical studies it could be shown that AMIC leads to a good clinical improvement of symptoms.…”
Section: Osteochondral Allograft Transplantationmentioning
confidence: 99%